Opportunities And Requirements for Responsibility for Application Software: A User Safety and Security Challenge - Monika Szyłkowska (Communications of International Proceedings, 2021)
This article covers reflection in the field of responsibility for application software as a user’s security challenge. The starting point for research was to find answers for crucial questions: what kind of liability have producers of application software? The question allowed the adoption of the initial thesis that liability for a software doesn’t exist in practice. The aim of the study was to analyze fundamental regulations in this matter [EU Directives in particular]. The results of the conducted research can make an important contribution to international research - in the context of the planned work on shaping the future security environment of network users at the global level. In the research process, was made extensive use of qualitative research methods, including analyses and methods: analysis and logical construction, generalization and implication. The source material included both open access and published studies in specialist journals.
Keywords: Users Security; Application Software; Liability for Software